The Skiving Stock Problem and its Application to Cognitive Radio Networks*. Issue 12 (2016) - Martinovic, John; Jorswieck, Eduard; Scheithauer, Guntram
Abstract: We consider the one-dimensional skiving stock problem (SSP) which is strongly related to the dual bin-packing problem in literature. In the classical formulation, different (small) item lengths and corresponding availabilities are given. We aim at maximizing the number of objects with a certain minimum length that can be constructed by connecting the items on hand. Such computations are of high interest in many real world applications, e.g. in industrial recycling processes, wireless communications and politico-economic challenges. After a short introduction to the SSP, one of these applications, the spectrum allocation in cognitive radio networks, is considered in more detail. As a main contribution, we present three modeling formulations for this problem that can cope with a particular additional constraint arising by hardware limitations, and provide numerical simulations for one of them.